Aplicación de la estrategia didáctica "Arquitectura de la Información" y su influencia en el Aprendizaje Cognitivo del Área Ciencia, Tecnología y Ambiente con estudiantes del segundo grado de educación secundaria en la Institución Educativa Nº 00884 - Los Olivos, distrito de Nueva Cajamarca - Flores Flores, Alida Esther (2007)
We are attending in an era of the information, characterized by the omnipresencia of the new technologies of the information and the communication; and the overabundance of the information. The abundance of information demands that the educative process develops in the students the capacities to look for, to select and to process the information. The education process learning has the urgent necessity to develop in the people the capacity of synthesis of the information that it qualifies to handle the information to him in good of the personal and social development. In syntheses of information, are important maps conceptual that plays role like tools of visual learning that allows the students to process, to organize and to prioritize new information, as well as to clarify their thought. From the perspective before described the investigation has been made whose objective was to validate the application of the didactic strategy "Architecture of the information" in the cognitive learning of the area Science, Technology and Atmosphere with students of the second degree of secondary education in 00884- Los the Educative lnstitution Nº Olive trees of the Nueva district Cajamarca. In order to reach to obtain this objective the hypothesis has settled down that the didactic strategy "Architecture of the information" will significantly influence in the cognitive learning of the students in the Area Science, Technology and Atmosphere of the second degree of secondary education in 00884-Los the Educative lnstitution Nº Olive trees of the Nueva district Cajamarca in 2006. The same one that has been resisted with if the didactic strategy "Architecture of the information" will not significantly influence in the cognitive learning of the students in the Area Science, Technology and Atmosphere of the second degree of secondary education in 00884- Los the Educative lnstitution Nº Olive trees of the Nueva district Cajamarca in 2006. The investigation of experimental type, of cuasiexperimental design, was carried out with 52 students of the second degree, of which 27 were of experimental group and 25 of the group control. To which a pretest was applied to them and postproves. The comparison of averages and variances by means of the normal distribution in Z has allowed to establish that the strategy "Architecture of the information significantly influences in the cognitive learning of the students in the Area Science, Technology and Atmosphere of the second degree of secondary education in 00884-Los the Educative lnstitution N° Olive trees of the Nueva district Cajamarca in 2006